Effectiveness the Influence of Deep Squat Exercise on the Acceleration of Cervical Dilation in Primigravida Mothers in the Active Phase of Labor - Jusmawati Jusmawati; Asniah Hartinah; Nur Fitriyah; Wahidah Wahidah; Sri Rahayu (GLOBAL HEALTH SCIENCE GROUP, 2026)
Prolonged labor in primigravida mothers is often caused by tension in the pelvic and cervical muscles that have never experienced stretching. Deep squat exercises are one of the non-pharmacological interventions based on an upright position that are utilized to assist in the descent of the fetal head and accelerate cervical dilation. Objective: To analyze the effect of deep squat exercises on the acceleration of cervical dilation in primigravida mothers during the active phase of the first stage of labor. Method: Quasi-experimental research with a two-group posttest-only control group design. The sample consisted of 30 primigravida parturients selected using purposive sampling in the active phase of the first stage of labor, divided into an intervention group (deep squat, n=15) and a control group (standard labor care/left lateral position, n=15). Analysis showed a significant difference in the number of mothers experiencing a fast labor duration during the active phase of the first stage of labor between the experimental group (n=11) and the control group (n=4). The results of the analysis using the nonparametric Kolmogorov-Smirnov test showed ρ=0.009 (ρ≤0.05), indicating that there is a significant effect of the deep squat position on the duration of the first stage of active labor. Conclusion: Deep squat exercises have a significant effect in accelerating the cervical dilation process in primigravida mothers during the active first stage of labor.